Hubungan Hygiene Sanitasi, Kepadatan Lalat dan Pengelolaan Limbah PAdat Dengan Kejadian Diare pada Rumah Susun Sukaramai Tahun 2014 - siti rahmah; irnawati marsaulina; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Diarrhea caused sickness and death in development country. Diarrhea is one of public heath problem Indonesia because diarrhea diseases included in the 10 diseases chich often caused high morbidity and mortality rates.This study aimed to describe the hygiene sanitation (water supply and sewerage), the density of flies and solid waste treatment with the incidence of diarrhea in sukaramai flats. Correlation beetwen the hygiene sanitation (water supply and sewerage), the density of flies and solid waste treatment with the incidence of diarrhea in sukaramai flatsThe type of study was analytic survey with cross sectional design. The sample of this study was 44 house wives who have a trash can on the house and this study conducted to sukaramai flats II Kecamatan Medan Area Kota Medan. Sample taken by Purposive sample methode. The results showed that the hygiene sanitation (water supply and sewerage) already qualified. The density of flies was low (0-2), so it doesn’t be a problem. But solid waste management still not qualified. There was significant relationship between water supply (p=0,001), the density of flies (p=0,001) with the incidence of diarrhea. Meanwhile, there was no relationship between sewerage (p=0,297), solid waste treatment (p=1) with the incindence of diarrhea. The hygiene sanitation ( water supply and sewerage) already qualified, but solid waste treatment aren’t qualified yet. Meanwhile, the density of flies was low. It suggested to people who live in sukaramai flats to keep the environment clean. Keyword : Diarrhea, water supply, sewerage, fly, solid waste.